2009
DOI: 10.1149/1.3133249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SnO[sub 2] Deposition Sequence in SnO[sub 2]-Modified PtRu/C Catalyst Preparation on Catalytic Activity for Methanol Electro-Oxidation

Abstract: SnO 2 -modified PtRu/C catalysts were prepared in a polyol process to investigate the effect of a SnO 2 deposition sequence on the catalytic activity for methanol electro-oxidation. The structure, morphology, and chemical state of the prepared catalysts were characterized by X-ray diffraction, scanning transmission electron microscopy, and X-ray photoelectron spectroscopy. The electrochemical activities were evaluated by cyclic voltammetry, linear sweep voltammetry, and chronoamperometry measurements in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…It is demonstrated that there are great improvements in terms of promotion effect or bifunctional effect when Pt was modified by other metals or metal oxides. The well-known studies claimed that the addition of metal oxides (TiO 2 [2], ZrO 2 [3], MoO 3 [4], CeO 2 [5,6], SnO 2 [7], etc.) effectively promotes the electrooxidation of methanol, their effect being attributed to two factors: (i) their ability to adsorb OH species, which are necessary for the oxidation of strongly adsorbed species to produce CO 2 [8,9]; (ii) an electronic effect that destabilizes the interactions of these species with the Pt sites [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that there are great improvements in terms of promotion effect or bifunctional effect when Pt was modified by other metals or metal oxides. The well-known studies claimed that the addition of metal oxides (TiO 2 [2], ZrO 2 [3], MoO 3 [4], CeO 2 [5,6], SnO 2 [7], etc.) effectively promotes the electrooxidation of methanol, their effect being attributed to two factors: (i) their ability to adsorb OH species, which are necessary for the oxidation of strongly adsorbed species to produce CO 2 [8,9]; (ii) an electronic effect that destabilizes the interactions of these species with the Pt sites [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In case of PtRu/SnO 2 /CNT platinum active sites may be further blocked by the SnO 2 particles. However these S EAS values look abnormally higher as compared to SnO 2 modified PtRu/C catalyst prepared by Wang et al despite of having a smaller particle size calculated from XRD [27]. A high value of S EAS for all the catalysts can be attributed to the porous structure of the catalyst support.…”
Section: Resultsmentioning
confidence: 69%
“…Once the CO ads on Ru sites were electro-oxidized, OH ads were produced on Ru sites at a faster rate than SnO 2 sites. During the methanol electro-oxidation, CO ads also could migrate from Pt sites to Ru sites [27], and therefore addition of SnO 2 with PtRu provides an additional route for OH ads formation and hence accelerates methanol oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Approaches to suppress CO adsorption has also been suggested; for example Rh-porphyline, 14 organic metal complexes 15 or metal oxides [16][17][18][19][20][21][22] have been proposed as additives to Pt-based catalysts.…”
mentioning
confidence: 99%
“…16 The water-gas shift reaction has been suggested to be responsible for the improvement in the CO tolerance of Pt/C modified with MoO x . 17,18 The SnO 2 modified PtRu/C [19][20][21][22] possessed improved cell performance under a high CO concentration of 500 ppm CO/H 2 , which was attributed to a combination of the promotional effect of SnO 2 and Ru species on CO tolerance. In many cases, the oxide additive partially covers the alloy surface and leads to a decrease in the electrochemically active PtRu surface area and thus the HOR activity.…”
mentioning
confidence: 99%